2022
DOI: 10.1016/j.simpa.2022.100218
|View full text |Cite
|
Sign up to set email alerts
|

AI-GlobalEvents: A Software for analyzing, identifying and explaining global events with Artificial Intelligence

Abstract: AI-GlobalEvents is a decision support dashboard for policy planners to conduct strategic threat assessments based on global news and events. It uses AI services and algorithms to automatically aggregate global news from online news portals, websites and social media for analyzing the events and identifying critical events requiring imminent attention. The software uses AI algorithms like Entity Detection, Sentiment Analysis, Anomaly detection and Regression to produce explanations in natural language. It is ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 6 publications
1
37
0
Order By: Relevance
“…The existing studies in political science, as seen in [4][5][6][7]21,22], have directly used location fields from Twitter feeds without applying a NER algorithm. Since this is the first study to apply a NER-based algorithm in the domain of political science, this study observed unique cases that have never been explored in previous studies [4][5][6]11,12,21,22,30]. During our experimentation, we witnessed several terms being incorrectly classified as location entities (i.e., false positives) and several valid location entities not being recognized as location entities (i.e., false negatives) by our implementation of NER algorithms.…”
Section: Discussionmentioning
confidence: 77%
See 4 more Smart Citations
“…The existing studies in political science, as seen in [4][5][6][7]21,22], have directly used location fields from Twitter feeds without applying a NER algorithm. Since this is the first study to apply a NER-based algorithm in the domain of political science, this study observed unique cases that have never been explored in previous studies [4][5][6]11,12,21,22,30]. During our experimentation, we witnessed several terms being incorrectly classified as location entities (i.e., false positives) and several valid location entities not being recognized as location entities (i.e., false negatives) by our implementation of NER algorithms.…”
Section: Discussionmentioning
confidence: 77%
“…NERs have been previously used in multiple domains, including the biomedical sector, as shown in [30]. In [30], researchers identified 14 articles that used NER exclusively within the biomedical In our previous studies, NER was used to generate locations of global events in a generic domain and not particularly focused on political science [11,12]. Moreover, in [17], our implementation of NER-based techniques was focused on the social science domain.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations